THE INFLUENCE OF HEALTH EDUCATION ABOUT SELF PROTECTION EQUIPMENT (MASK) ON THE KNOWLEDGE OF FURNITURE WORKERS IN "UD" RIMBA KARYA AT MOROSUNGGINGAN VILLAGE KEC PETERONGAN KAB JOMBANG - Asbanu, Zeth; Na'im, Semi; Puspita, Enny (PRIMA WIYATA HEALTH, 2020)
Unhealthy working environment can become a problem to work, workers that haven't used mask while working because lack of knowledge about the importance of self protection equipment (mask).This research has a purpose to know The Influence Of Health Education About Self Protection Equipment (Mask) On The Knowledge Of Furniture Workers In "UD" RIMBA KARYA At Morosunggingan Village Kec Peterongan Kab Jombang The research design used Pre Experimental with One Group Pre-Post Test Design approach, the population were 30 respondents, the sample used were 30 respondents with total sampling. independent variable was health education, dependent variable was knowledge. The research instrument used questionnaires, data analysis using Wilcoxon Signed Ranks statistical test with α = 0.05. The research result before being given health education about self protection equipment (mask) to the knowledge of furniture workers showed less knowledge than 20 respondents (66%) of 30 respondents, then after being given health education about self protection equipment (mask) to the knowledge of furniture workers showed good knowledge a number of 21 respondents (70%) out of 30 respondents. Wilcoxon Signed Ranks statistical test results showed ρ value = 0.001, Ha was accepted, that meant there was The Influence Of Health Education About Self Protection Equipment (Mask) On The Knowledge Of Furniture Workers In "UD" RIMBA KARYA At Morosunggingan Village Kec Peterongan Kab Jombang. Providing health education can increase the knowledge of furniture workers who work in the "UD" Rimba Karya so that nurses are expected to provide health education to furniture workers who work in the 'UD "Rimba Karya once a month so that furniture workers stay using swlf protection equipment (mask) while working .